Generalized granulomatous inflammation caused by Candida lusitaniae in a patient with myelofibrosis - Yu. S. Korneva; O. V. Azovskova; O. A. Shisterova (Онкогематология, 2019)
This article describes a clinical case demonstrating the difficulties of lifetime and post-mortem diagnosis in a patient with primary myelofibrosis complicated by a generalized fungal infection caused by a rare pathogen such as Candida lusitaniae. Management of such patients in non-specialized department with absence of bone marrow trepanobiopsy results associated with the variety of clinical situations in which such manifestations as neutrophilic leukocytosis with left shift without significant changes in the number of erythrocytes and platelets simultaneously with lymphadenopathy and visualizations of secondary foci in internal organs leads to wrong treatment management. And superposition of several pathological processes (granulomatous inflammation, foci of extramedulary hemopoesis and extensive necrotic changes) causes difficulties even for post-mortem verification of the diagnosis, that demonstrate the interest of this clinical case.